2010
DOI: 10.3109/13550280903559789
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral biomarkers do not correlate with cognitive impairment in highly active antiretroviral therapy–treated subjects with human immunodeficiency virus type 1 infection

Abstract: Neuropsychological (NP) impairments in human immunodeficiency virus (HIV)-infected individuals remain high despite the introduction of highly active antiretroviral therapy (HAART). We sought to determine whether or not a monocyte gene expression profile along with other peripheral factors would correlate with neuropsychological impairment among HIV-infected individuals. Forty-four HIV-1-seropositive subjects (HIV+) on HAART and 11 HIV-1-seronegative controls (HIV-) had NP testing and blood drawn for monocyte g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 42 publications
4
39
1
1
Order By: Relevance
“…We previously reported a type 1 interferon (IFN)-α-driven monocyte phenotype in individuals with chronic HIV infection that correlated with viral load [9,10]. Here, we show that a monocyte IFN-α activation profile and IFN-gamma-inducible protein-10 (IP-10, CXCL10) in the plasma of HIV-positive individuals correlated with lower concentrations of NAA in the frontal white matter (FWM) measured by 1 H MRS.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…We previously reported a type 1 interferon (IFN)-α-driven monocyte phenotype in individuals with chronic HIV infection that correlated with viral load [9,10]. Here, we show that a monocyte IFN-α activation profile and IFN-gamma-inducible protein-10 (IP-10, CXCL10) in the plasma of HIV-positive individuals correlated with lower concentrations of NAA in the frontal white matter (FWM) measured by 1 H MRS.…”
Section: Introductionmentioning
confidence: 62%
“…All HIV-positive individuals were on stable ART or treatment interruption. Neuropsychological testing assessed seven domains of cognitive function and cognitive impairment was defined as more than 1.5 SD below the norm in at least two domains [9]. A global deficit score (GDS) was calculated with 0 being normal and a GDS at least 0.5 defined as mildly impaired [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although such markers have been correlated to disease activity, they have not been clinically used for diagnosis or monitoring of Neuro-AIDS owing to lack of specificity for active neurological disease in the setting of the immune activation characterizing HIV infection (Gisslén et al 2009). Recently, attention has turned to plasma markers related to immunopathogenesis of systemic HIV, including soluble CD14 and lipopolysaccharide (Ancuta et al 2008;Sun et al 2010). Direct markers of neurological injury assayed in CSF, including neurofilament light chain protein (NFL), tau protein, and precursors and products of amyloid protein (amyloid precursor proteins and Ab1-42) may be more valuable as measures of active neurodegeneration or injury (Hagberg et al 2000;Gisslen et al 2007Gisslen et al , 2009Clifford et al 2009).…”
Section: Biomarkers Of Cns Diseasementioning
confidence: 99%
“…7,8 Although there is still limited evidence in the literature determining the role of CD8 T cells in HIV-related NCI, studies have suggested CD8 lymphocytes may be a possible marker for inflammation, which is believed to be a contributing factor to NCI. 9,10 The recent observation of CD4:CD8 ratio association with markers of age-associated disease in virally suppressed individuals with immunological recovery 11 strengthens the requirement for data on the role of CD8 T cells in NCI.…”
Section: Introductionmentioning
confidence: 99%